Predicting Laboratory Scale Permeability on Berea Sandstone Thin Section using 3D Porous Media Reconstruction and Upscaling Method - Lubis, Luluan Almanna (2012)
Present paper describes a new approach to predict laboratory scale permeability using information of thin section image. The workflow was applied on Berea sandstone thin section which has similar length as the measured core plug. In this workflow, instead of using a part of thin section, full thin section image was used as an input to predict permeability at laboratory scale. The workflow is using 3D porous media reconstruction method to estimate permeability at pore scale level. To define heterogeneities at laboratory scale on full thin section image, grain size vertical profile was calculated. Building blocks were determined based on grain size vertical profile trends. Upscaling from pore to core plug scale was applied on full thin section image of Berea sandstone. Permeability at laboratory scale was calculated and the results match well with accuracy ~85 compare to laboratory data.